2013
DOI: 10.1016/j.bbamcr.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Specificity protein 4 functionally regulates the transcription of NMDA receptor subunits GluN1, GluN2A, and GluN2B

Abstract: N-methyl-d-aspartate (NMDA) receptors are major glutamatergic receptors involved in most excitatory neurotransmission in the brain. The transcriptional regulation of NMDA receptors is not fully understood. Previously, we found that the GluN1 and GluN2B subunits of the NMDA receptor are regulated by nuclear respiratory factors 1 and 2 (NRF-1 and NRF-2). NRF-1 and NRF-2 also regulate all 13 subunits of cytochrome c oxidase (COX), a critical energy-generating enzyme, thereby coupling neuronal activity and energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…When incubated with mouse visual cortical tissue nuclear extract, GM3 synthase formed specific DNA/Sp3 and DNA/Sp4 shift and supershift complexes (Figure 1, lane 1 for Sp3/Sp4 shift, lanes 4 and 5 for Sp3 and Sp4 supershift, respectively) but did not form a DNA/Sp1 shift or supershift complex (Figure 1, lanes 1 and 3 respectively). The lack of a strong Sp4 supershift with HeLa nuclear extract as compared to mouse visual cortical nuclear extract is consistent with our previous observations of different levels of Sp4 abundance in the two nuclear extracts and with its reported neuronal distribution [19, 28]. Similarly, the lack of Sp1 shift or supershift with mouse cortical nuclear extract as compared to HeLa nuclear extract was due to the lower abundance of Sp1 in mouse cortical nuclear extract as compared to HeLa nuclear extract [28].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…When incubated with mouse visual cortical tissue nuclear extract, GM3 synthase formed specific DNA/Sp3 and DNA/Sp4 shift and supershift complexes (Figure 1, lane 1 for Sp3/Sp4 shift, lanes 4 and 5 for Sp3 and Sp4 supershift, respectively) but did not form a DNA/Sp1 shift or supershift complex (Figure 1, lanes 1 and 3 respectively). The lack of a strong Sp4 supershift with HeLa nuclear extract as compared to mouse visual cortical nuclear extract is consistent with our previous observations of different levels of Sp4 abundance in the two nuclear extracts and with its reported neuronal distribution [19, 28]. Similarly, the lack of Sp1 shift or supershift with mouse cortical nuclear extract as compared to HeLa nuclear extract was due to the lower abundance of Sp1 in mouse cortical nuclear extract as compared to HeLa nuclear extract [28].…”
Section: Resultssupporting
confidence: 92%
“…The lack of a strong Sp4 supershift with HeLa nuclear extract as compared to mouse visual cortical nuclear extract is consistent with our previous observations of different levels of Sp4 abundance in the two nuclear extracts and with its reported neuronal distribution [19, 28]. Similarly, the lack of Sp1 shift or supershift with mouse cortical nuclear extract as compared to HeLa nuclear extract was due to the lower abundance of Sp1 in mouse cortical nuclear extract as compared to HeLa nuclear extract [28]. The shift bands for visual cortical and HeLa nuclear extract were competed out with the addition of cold competitors (Figure 1, lanes 2 and 7, respectively).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the mechanism(s) underlying impaired motivation and learning resulting from reduced Sp4 expression have yet to be delineated. As SP4 regulates the transcription of NMDA receptor subunits GluN1, GluN2A, and GluN2B (Priya et al, 2014;Priya et al, 2013), further investigation of other mechanisms using these mice is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that for many genes, transcript and protein levels do not correlate well (Tian et al 2004). However, there are some reports that transcript levels of the GluN1 subunit are correlate with its protein levels (Jayanthi Priya et al 2013). In addition, it has been recently reported that complete deletion of the obligatory GluN1 subunit of the NMDA receptors in hippocampal slice cultures completely eliminates NMDA receptors (Incontro et al 2014).…”
Section: Days After Bdlmentioning
confidence: 97%